Agenesis of distal segment of right vertebral artery: a case report. - Chauhan, R; Khatri, K; Gambhir, M (Department of Surgery, UKM Medical Centre, 2012)
A case is being reported in which the basilar artery was formed only by the left vertebral artery. This was detected incidentally in a female on a non contrast magnetic resonance angiogram. The right vertebral artery arose as a direct branch of the right subclavian artery but terminated blindly at the level of second cervical vertebra. The left vertebral artery which contributed to the formation of basilar artery continued as left posterior cerebral artery while right posterior cerebral artery was seen as a continuation of right posterior communicating artery. The knowledge of variations of the vertebrobasilar arterial complex is important to Clinicians, Radiologists and Surgeons operating on the great vessels and its branches, particularly vascular surgeons dealing with vertebral artery in order to prevent a vascular catastrophe.